Delamination strength of composite curved beams reinforced by grooved stainless-steel Z-pins. (15th November 2017) - Ju, Hyunwoo; Nguyen, Khanh-Hung; Chae, Song-Su; Kweon, Jin-Hwe
Abstract: When a laminated composite structure with curvature is subjected to a bending load, the most important failure mode is due to delamination in curved regions. In this study, the reinforcement effect of grooved Z-pins is investigated for preventing delamination of curved beams. Through a four-point bending test, the effect of stainless-steel pin diameter and areal density on bending failure of curved beams is studied. For areal pin densities of 0.5, 1.0, and 2.0%, pin diameters of 0.3 and 0.5 mm result in average pin strength increases of 21, 27, and 42% and 8.7, 12, and 32%, respectively. When the pin size is small, the pin is inserted closer to 90° from the mid-plane, a smaller resin-rich zone is generated, and there is less laminate damage.